"Conformation pinning" by anion attachment enabling separation of isomeric steroid monomers by ion mobility spectrometry. (11th October 2020) - Cole, Richard B.; Bayat, Parisa; Murray, Jane S.; Albers, Christian; Brombach, Dorith
Abstract: The separation of small molecule isomers has become a proving ground for ion mobility spectrometry (IMS). To date, successful IMS separation of steroid isomers has been accomplished largely by examination of alkali metal cationized dimers, with few examples of successful separations of monomeric steroid isomers in either positive or negative ion modes. Here, we report on the novel use of anion attachment to form negative ion monomeric adducts of steroid isomers that may be separated by IMS. Computational modeling shows that [prednisolone + Cl] − adopts a conformation wherein the attaching chloride is chelated between two hydroxyl hydrogens. The electrostatic interaction between Cl − and the two substituent electropositive hydroxyl hydrogens causes "conformation pinning" of prednisolone, thereby forcing the complex to adopt a constricted conformation. The tighter conformation of [prednisolone + Cl] − permits baseline IMS separation from its isomer [cortisone + Cl] − that exists only in elongated form. Although distinguishable as anionic adducts, these isomeric steroids were impossible to separate as either protonated (MH +, positive mode) or deprotonated ([M‐H] −, negative mode) analogs. Another pair of isomeric steroids 21‐deoxycortisol and corticosterone showed improved IMS separations as chloride adducts as compared to the analogous MH + or [M‐H] − pairs. Lastly, success was shown in separating protonated dimeric forms of isomeric steroid pairs by IMS, and we distinguish these separations from those of alkali metal cationized dimers that have been previously reported.